Arthroscopy Limits on Anterior Shoulder Instability - Jair Simmer Filho; Raul Meyer Kautsky (Revista Brasileira de Ortopedia, 2022)
Abstract Much is discussed about the limits of the treatment of anterior shoulder instability by arthroscopy. The advance in understanding the biomechanical repercussions of bipolar lesions on shoulder stability, as well as in the identification of factors related to the higher risk of recurrence have helped us to define, more accurately, the limits of arthroscopic repair. We emphasize the importance of differentiation between glenoid bone loss due to erosion (GBLE) and glenoid edge fractures, because the prognosis of treatment differs between these forms of glenoid bone failure. In this context, we understand that there are three types of bone failure: a) bone Bankart (fracture); b) combined; and c) glenoid bone loss due to anterior erosion (GBLE), and we will address the suggested treatment options in each situation. Until recently, the choice of surgical method was basically made by the degree of bone involvement. With the evolution of knowledge, the biomechanics of bipolar lesions and the concept of glenoid track, the cutoff point of critical injury, has been altered with a downward trend. In addition to bone failures or losses, other variables were added and made the decision more complex, but a little more objective. The present update article aims to make a brief review of the anatomy with the main lesions found in instability; to address important details in arthroscopic surgical technique, especially in complex cases, and to bring current evidence on the issues of greatest divergence, seeking to guide the surgeon in decision making.